Development of conductive bacterial cellulose foams using acoustic cavitation - Vadanan, Sundaravadanam Vishnu (2022)
Bacterial cellulose (BC) has found applications in various fields ranging from healthcare to electronics. Functionalization of cellulose to impart conductive properties has been met with challenges due to superficial coating rather than uniform interactions with the conducting polymers. In this work, mechanical disruption is shown to be a facile strategy to develop BC-PEDOT:PSS conductive foams without the use of any harsh chemical treatments to functionalize cellulose. The strategy allows for uniform polymer intercalation with the cellulose nanofibers imparting superior conductive properties to the functional material. The conductive foams with low PEDOT:PSS ratio exhibit conductivity of 0.7 S/cm and are cytocompatible with human dermal fibroblasts (HDFa) cells.